Advantage of proton-radiotherapy for pediatric patients and adolescents with Hodgkin’s disease - Lautenschläger, Friedrich Stefan; Iancu, G.; Flatten, V.; Baumann, K.; Thiemer, M.; Dumke, C.; Zink, K.; Hauswald, Henrik; Vordermark, Dirk; Mauz-Körholz, Christine; Engenhart, Rita; Eberle, F. (Radiation oncology, 2019)
Radiotherapy is frequently used in the therapy of lymphoma. Since lymphoma, for example Hodgkin’s disease, frequently affect rather young patients, the induction of secondary cancer or other long-term adverse effects after irradiation are important issues to deal with. Especially for mediastinal manifestations numerous organs and substructures at risk play a role. The heart, its coronary vessels and cardiac valves, the lungs, the thyroid and, for female patients, the breast tissue are only the most important organs at risk. In this study we investigated if proton-radiotherapy might reduce the dose delivered to the organs at risk and thus minimize the therapy-associated toxicity.
Gesehen am 21.01.2020